Enhanced lignin extraction from different species of oil palm biomass: Kinetics and optimization of extraction conditions - Rashid, T. (Elsevier B.V., 2018)
Lignin from industrial crops is a renewable bioresource which can be used for a variety of value-added applications, however effective separation of lignin from lignocellulosic biomass is still an ongoing challenge. The present study involves the selective extraction of lignins from three different morphological parts of oil palm biomass plant, namely empty fruit bunches (EFB), palm mesocarp fiber (PMF) and palm kernel shells (PKS) using Pyridinium Formate PyFor, a Protic ionic liquid under mild extraction conditions compared to the conventional chemical processes. The effect of initial lignin contents and parameters (namely, particle size range, extraction temperature, time and solid loading) influencing the lignin extraction efficiency were analyzed and optimized using response surface methodology. The experiments conducted at the estimated optimum conditions gave the maximum lignin extraction of 92.01%, 91.23% and 90.70% at lowest process temperatures 351.5 K, 361.9 K and 370.8 K for EFB, PMF and PKS respectively. In a second-stage the extraction experiments were conducted to study the kinetics of extraction process under selected conditions and results were well correlated using pseudo-second order kinetics model. The theoretical lignin concentration at saturation (Cs), rate constant (K) and initial rate of extraction (h) at various temperatures ranging from 323 to 373 K were determined. The nature of biomass source and initial lignin content were found to have major impact on the extraction kinetics. Furthermore, the present estimated activation energies of 12 kJ molâ1, 23 kJ molâ1 and 28 kJ molâ1 for the present extraction of lignins from EFB, PMF and PKS respectively are remarkably lower as compared to those reported in literature for traditional wood pulp processes. The extracted lignins were successfully characterized using FTIR and 1H NMR analysis. The regeneration and recyclability of PyFor is also tested and the sustainability of the solvent for commercial application is proved. Â© 2018 Elsevier B.V.